의학전문대학원생의 발표기술 향상 프로그램 개발 및 교육 효과 - 박귀화(Kwi Hwa Park); 박이병(Ie Byung Park) (Korean journal of medical education, 2011)
Purpose: The purpose of this study was to develop and examine a program that was designed to improve the presentation skills of medical school students. Methods: The program was implemented in 2-day workshops for 36 third-grade medical students in 2009, using the following procedures in order: needs assessment; an initial group presentation and peer evaluation; an initial self-evaluation with video recording; viewing of a model presentation; a second presentation in a group and peer evaluation; and a second self-assessment. Two types of survey questionnaires were used: a self-evaluation checklist and a questionnaire on workshop satisfaction and confidence of presentation. Results: Eighty-three percent of the students recognized the importance of presentation skills. There were significant differences in 3 factors of self-evaluation-constructing contents, utilizing audio-visual media, and delivery skills- but not with regard to understanding content. In the post workshop satisfaction survey, participants reported that the workshop was helpful in improving their own presentation skills. They also stated that presentation in a group, peer feedback, and video analysis of the recording were helpful. After the workshop, students claimed that their confidence scores in utilizing audio-visual media were the highest. Conclusion: Medical students realize the importance of presentation skills training and workshops in increasing presentation skills and improving confidence in presenting. Video analysis and feedback of each participant's presentation within the group was effective in upgrading the student's presentation skills. Purpose: The purpose of this study was to develop and examine a program that was designed to improve the presentation skills of medical school students. Methods: The program was implemented in 2-day workshops for 36 third-grade medical students in 2009, using the following procedures in order: needs assessment; an initial group presentation and peer evaluation; an initial self-evaluation with video recording; viewing of a model presentation; a second presentation in a group and peer evaluation; and a second self-assessment. Two types of survey questionnaires were used: a self-evaluation checklist and a questionnaire on workshop satisfaction and confidence of presentation. Results: Eighty-three percent of the students recognized the importance of presentation skills. There were significant differences in 3 factors of self-evaluation-constructing contents, utilizing audio-visual media, and delivery skills- but not with regard to understanding content. In the post workshop satisfaction survey, participants reported that the workshop was helpful in improving their own presentation skills. They also stated that presentation in a group, peer feedback, and video analysis of the recording were helpful. After the workshop, students claimed that their confidence scores in utilizing audio-visual media were the highest. Conclusion: Medical students realize the importance of presentation skills training and workshops in increasing presentation skills and improving confidence in presenting. Video analysis and feedback of each participant's presentation within the group was effective in upgrading the student's presentation skills. KCI Citation Count: 4